Penicillin-Binding Protein 1 of Staphylococcus aureus Is Essential for Growth - Wada, Akihito (American Society for Microbiology, 1998)
pbpA, a gene encoding penicillin-binding protein (PBP) 1 of Staphylococcus aureus, was cloned in an Escherichia coli MC1061 transformant which grew on a plate containing 512 μg of vancomycin per ml. This gene encodes a 744-amino-acid sequence which conserves three motifs of PBPs, SXXK, SXN, and KTG. The chromosomal copy of pbpA could be disrupted only when RN4220, a methicillin-sensitive S. aureus strain, had additional copies of pbpA in its episome. Furthermore, these episomal copies of pbpA could not be eliminated by an incompatible plasmid when the chromosomal copy of pbpA was disrupted beforehand. Based on these observations, we concluded that pbpA is essential for the growth of methicillin-sensitive S. aureus.